The use of specialized training techniques to maximize muscle hypertrophy - Schoenfeld, B. (Strength and Conditioning Journal, 2011)
A variety of specialized training techniques have been advocated as a means to heighten muscle growth. Forced repetitions/drop sets, supersets, and heavy negatives, in particular, have been purported to enhance the hypertrophic response to resistance exercise. This article will explore the potential role of these techniques in promoting muscle hypertrophy and provide an insight into possible applications to resistance training programs.